At an important tephrostratigraphic crossroads: cryptotephra in Late Glacial to Early Holocene lake sediments from the Carpathian Mountains, Romania - Kearney, RJ; Albert, PG; Staff, RA; Magyari, EK; Pál, I; Veres, D; Lane, CS; McGuire, A; Ramsey, CB (Elsevier, 2024)
Understanding the temporal and spatial environmental response to past climate change during the Last Glacial-Interglacial Transition (LGIT, 16-8 ka) across Europe relies on precise chronologies for palaeoenvironmental records. Tephra layers (volcanic ash) are a powerful chronological tool to synchronise disparate records across the continent. Yet, some regions remain overlooked in terms of cryptotephra investigations. Building on earlier work at the same sites, we present the first complete LGIT high-resolution cryptotephra investigation of two lake records in the Carpathian Mountains in Romania, Lake Brazi and Lake Lia. Numerous volcanic glass shards have been recognised as originating from various volcanic regions, including: Iceland (Katla, Askja, and Torfajokull), Italy (Campi Flegrei, Ischia, Lipari, and Pantelleria), and central Anatolia (Acigol and Ericyes). In total, four distinct tephra horizons have now been identified in these records: 1) an LGIT Lipari tephra (11,515–12,885 cal BP, 95.4% range); 2) Askja-S (11,070–10,720 cal BP, 95.4% range); 3) an Early Holocene Lipari tephra,(12,590–10,845 cal BP, 95.4% range) and; 4) an Early Holocene Ischia tephra (11,120–10,740 cal BP, 95.4% range). The use of trace element analysis on selected cryptotephra layers provided additional important information in identifying volcanic source and facilitating correlations. These tephra layers, along with numerous other discrete cryptotephra layers, offer promise as significant future isochrons for comprehending the spatial and temporal fluctuations in past climate change throughout Europe and the Mediterranean area. This research has emphasized the significance of the Carpathian region in expanding the European and Mediterranean tephra lattice and establishing it as a keystone area within the framework.